Locally-led and co-designed adaptation solutions, including monitoring indicators - Jimenez, Maria de los Angeles; Clavijo, Neidy; Rodriguez, Luz Angela; Vanegas Cubillos, Martha (2025)
In order to contribute to the co-creation and implementation of locally led adaptation (LLA) innovations and participatory decision-making processes that strengthen local capacities and promote social inclusion, We structured the process around four strategic pillars: (i) participatory diagnosis of climate risks, (ii) consolidation of co-designed adaptation solutions, (iii) definition of prioritization criteria, and (iv) establishment of indicators for the 2025–2027 roadmap. The purpose is to contribute to the construction innovation pathway for LLA, along with the co-design of a community-based research agenda for transforming food systems.